Marketing Feasibility and Strategic Application of the Marketing Mix in Small Retail Enterprises: A Case Study of Toserba 35 Hidayah, West Sumatra - Lucky Mahesa Yahya; Ayu Putri Radinda; Widya Kartika Asri; Muhammad Ilham; Andreza Yosmi Saputra (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
This study aims to analyze the marketing feasibility and application of the marketing mix (4P: product, price, place, and promotion) in the operation of Toserba 35 Hidayah, a local retail enterprise in Lima Puluh Kota, West Sumatra. Using a qualitative descriptive approach, data were collected through in-depth interviews, direct observation, and document review to assess the firm’s competitive position and market strategy. The findings indicate that the business demonstrates strong marketing feasibility supported by product diversity, strategic location, competitive pricing, and customer-oriented service. However, the promotional strategy remains traditional, relying primarily on word-of-mouth, indicating the need for digital marketing adoption to expand market reach. The study concludes that integrating modern marketing practices—particularly social media engagement and customer loyalty programs—would enhance competitiveness and sustainability. Theoretically, this research reinforces the role of the marketing mix as a determinant of micro-enterprise performance and highlights the importance of adaptive marketing innovation in the Indonesian retail sector.